Pengaruh Overconfidence dan Literasi Keuangan Syariah Terhadap Keputusan Investasi - Syifa Rohmah (Journal of Islamic Economics and Finance, 2023)
The purpose of this research was to determine the effect of overconfidence, Islamic financial literacy on investment decisions in MSMEs in Semarang City. This research is a quantitative research using primary data. The method of data collection was carried out through a questionnaire distributed to UMKM in the city of Semarang. The sample used in this research was 100 respondents with a purposive sampling technique. The data obtained was processed with SPSS. This analysis uses instrument test, multiple linear regression test, t test, f test, R2 test, and classical assumption test. Based on the results of the T test, overconfidence and financial literacy have a positive effect on investment decisions. The results of the F test show that overconfidence and financial literacy simultaneously have a significant positive effect on investment decisions.